From learning to the habit: adoption of oral health knowledge by foster mothers in the family environment - Giraldo-Zuluaga, Maria Cristina; Lopera-Escobar, Alejandra; Sepúlveda-Drosos, Laura Daniela (Revista Facultad de Odontología Universidad de Antioquia, 2025)
Introduction: Oral health is recognized as a component of overall well-being, and promoting it within the family environment contributes to the prevention of common diseases. In foster families, there is the additional challenge of instilling healthy habits in children who, in many cases, did not acquire these habits in their homes of origin. The objective was to analyze the adoption of oral care knowledge and practices by foster families participating in the Healthy and Smiling Families program, which promotes mothers' leadership as primary caregivers of oral health in the home. Methods: A qualitative study with an ethnographic approach included semi-structured interviews with 14 foster mothers, participant observation, and the administration of knowledge questionnaires before and after the intervention. Results: Participants demonstrated the adoption of practices such as frequent brushing, flossing, and regular dental checkups. Furthermore, mothers recognized their role as health promoters within their families. Educational and recreational activities, differentiated by age group, facilitated the participation of all household members. An increase in knowledge scores was observed between the initial and final measurements. Conclusion: Pregnant mothers strengthened their ability to lead family oral care. This intervention model, based on ongoing support, contextualization, and participation, was established as an effective strategy for achieving sustainable changes in self-care and promoting healthy habits within the family environment.